Embedding Green Product Attributes Preferences and Cultural Consideration for Product Design Development: A Conceptual Framework - Ihwan Ghazali, Ihwan Ghazali; Abdul-Rashid, Salwa Hanim; Md Dawal, Siti Zawiah; Irianto Irianto, Irianto Irianto; Herawan, Safarudin Gazali; Fu-Haw Ho, Fu-Haw Ho; Abdullah, Rohana; Abdul Rasib, Amir Hamzah; Sufina Padzil, Nur Wardah
In the past ten years, the increasing customer awareness of environmental sustainability has driven the development of green products. As the initiator of product development, this situation can challenge product designers. Since customers may have varied expectations and preferences for green products, it depends on the green attributes embedded in the product and cultural value influences. As the natural behavior setting, cultural value has been proven to influence customer preferences in the literature. However, it was identified that previous studies had not clearly defined the consideration of cultural values in green product design. Therefore, this study aimed to generate a conceptual framework for embedding cultural value consideration in green product design. A comprehensive review of green product design and cultural values has been performed to align the relevancies for constructing the conceptual framework. Bibliographic analysis using the PRISMA approach was also performed to identify the current trend of green product design. It was expected that the proposed conceptual framework could be used as supporting insight in determining the customers’ preferences as an essential process for green product development